MENGATASI PERSOALAN POLITIK IDENTITAS DI INDONESIA MELALUI PEMIKIRAN AHMAD SYAFII MAARIF - Josep Aldo Setiawan (Integritas Terbuka: Peace and Interfaith Studies, 2026)
This study analyzes Ahmad Syafii Maarif’s thought on the relationship between Islam, the state, and nationhood and examines its relevance for addressing identity politics in contemporary Indonesia. This study is important because the mobilization of religious identities in the political arena has the potential to intensify social polarization and undermine national integration within a plural society. The study employs a qualitative approach using a library research method. The data consist of Ahmad Syafii Maarif’s major works and relevant academic literature, which are analyzed through Hassan Hanafi’s theory of Al-Turath wa al-Tajdid and Abdul Karim Soroush’s theory of Qabdh wa Bast. The findings show that Ahmad Syafii Maarif rejects the concept of ad-din wa ad-daulah because religion and the state possess fundamentally different characteristics. Religion is normative and transcendent, whereas the state is historical, dynamic, and open to change. In his view, Islam should function as a source of public ethics that guides national life, while the principle of shura serves as a meeting point between Islamic values, democracy, and Indonesian nationalism. Based on this perspective, Ahmad Syafii Maarif develops the concept of National Islam (Islam Kebangsaan), which places pluralism, justice, and humanity at the center of collective life. This concept offers an alternative to exclusive and sectarian forms of identity politics. This study contributes to the literature by demonstrating that National Islam represents a synthesis between the reconstruction of Islamic tradition and a contextual understanding of religion that can serve as a normative framework for strengthening democracy and social cohesion in Indonesia.